Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1149/2.021301jes
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Factors Affecting the Formation of Carbonyl Iron Electrodes in Rechargeable Alkaline Iron Batteries

Abstract: Rechargeable iron-based alkaline batteries such as iron -air and nickel -iron batteries are attractive for large-scale electrical energy storage because iron is inexpensive, globally-abundant and environmentally-friendly. Further, the iron electrode is known for its robustness to repeated charge/discharge cycling. During manufacturing these batteries are charged and discharged 20 to 50 times during which the discharge capacity of the iron electrode increases gradually and attains a stable value. This process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 40 publications
(69 reference statements)
4
82
0
Order By: Relevance
“…These observations are also consistent with the model for the formation of the iron electrode that we have proposed in previous studies on the pressed-plate type iron electrode. 43 We also examined the morphology of sintered iron electrode that had passivated in the absence of sulfide under the conditions of constant current discharge. While the overall electrode structure was still porous (Figure 10a), the compact morphology (Figure 10b) suggested no significant formation of the discharged phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations are also consistent with the model for the formation of the iron electrode that we have proposed in previous studies on the pressed-plate type iron electrode. 43 We also examined the morphology of sintered iron electrode that had passivated in the absence of sulfide under the conditions of constant current discharge. While the overall electrode structure was still porous (Figure 10a), the compact morphology (Figure 10b) suggested no significant formation of the discharged phase.…”
Section: Resultsmentioning
confidence: 99%
“…17,43,44 In our previous studies, we have demonstrated the benefits of using bismuth sulfide and iron sulfide in achieving high discharge rates on iron electrodes. 17,44 In this study of the sintered iron electrode, the effects of soluble sodium sulfide additive and iron sulfide have been studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, different electrode formulation additives have been utilised to achieved that aim, including bismuth [28], bismuth sulphide [26], carbonaceous materials [29e31], iron oxide [32,33], etc. Undoubtedly, the development of sulphur based iron electrode formulations is one of the most promising alternatives [25]. Moreover, the performance of the NiFe cells can also be further improved by optimising the electrolyte composition; in fact, different electrolyte additives such as wetting agents [34], long chain thiols [35], organic acids [36], among others have been investigated.…”
Section: Introductionmentioning
confidence: 99%